Media Literacy in Increasing Reading Interest - R. P. Tutiasri; S.N. Febriyanti; A. Kusuma (Future Science)
Survey of national library in 2015 shows that 90% of Indonesian society prefer watching television rather than reading. This preference is also popular among kids and teens in Kemlagi village, Mojokerto. The appearance of shopisticated technology is influencing reading interest among kids and teens, they are so enganged with their gadget rather than playing or reading. In fact, in using technology, people do not need to read, but a habit and observation. This statement can be proven by seeing a child who able to operate a mobile phone. Besides, smartphone facilitate children to find a motioning picture on Youtube, they can operate a phone or certain application without reading a book to know how an application works. In addition parents are supporting their kids by letting them using their phone rather than reading. This statement can be seen by a number of parents who buying their kids a phone rather than a book. Low interest in reading is influenced by inadequate facilities and illiterate society in that village. Therefore, community service of PIKAT UPN “Veteran” East Java has been enganging a partnership with Empowerment-Development and Family Welfare (PT-PKK) Association of Kemlag, Kemlagi, Mojokerto Regency to hold a media literacy socialization and establish a rural library as an effort in increasing reading interest. Outcomes of this activities are the avaibility of rural library facilities in Kemlag, Kemlagi, Mojokerto Regency, eradicating illiteracy strategy, and published scholarly article in proceeding.